The Role of Physical Activity in the Management of Treatment-Resistant Depression: Evidence and Future Directions - Klonowska, Justyna; Kosek, Szymon; Walkowski, Radosław Jan; Wasiniewska, Weronika; Barański, Marcin; Kandefer, Tomasz; Sroka, Maria Izabela (Quality in Sport, 2025)
Treatment-resistant depression (TRD) is a clinical condition characterized by failure to achieve remission after at least two trials of different antidepressants given at adequate doses and duration. It affects about 30% of patients who suffer from major depressive disorder (MDD), which makes it a big public health challenge by its association with increased morbidity, impaired functioning and reduced quality of life. Novel treatment methods like ketamine, esketamine, psychostimulants, and neuromodulation, have improved management of MDD but many patients continue to experience persistent symptoms. Physical activity has demonstrated therapeutic benefits in depression treatment with its influence on biological pathways by means of neuroplasticity, neurotransmitter modulation, and immune regulation. It is a low-cost, accessible intervention with additional physical and psychosocial advantages. Evidence from clinical trials and meta-analyses suggests that various exercise types including aerobic, resistance, and mind-body training significantly reduce depressive symptoms and improve quality of life in patients struggling with depression. However, specific studies on physical activity in TRD are limited, with promising ongoing trials (e.g., TRACE-RMD) investigating its efficacy as an adjunctive treatment. Incorporating exercise into standard treatment algorithms for TRD might yield positive outcomes and be valuable compliment to pharmacotherapy and psychotherapy but we still lack scientific data. Taking into consideration high prevalence and significant burden of TRD further research is needed. Creating and standardizing exercise protocols, improving adherence, and understanding long-term outcomes should be the goal of future studies.